ANALYSE FACTORS INFLUENCING CONSUMER PERCEPTION AND PURCHASE INTENTIONS FOR ELECTRIC VEHICLES IN THE INDIAN AUTOMOBILE INDUSTRY - Narayani, Kumar Nambi; N. Hariprakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The transition to electric vehicles (EVs) is emerging as a sustainable solution to address environmental degradation and rising fuel costs. This study examines the variables affecting consumers’ perceptions of and intentions to buy electric vehicles in the Tamil Nadu auto industry. Data were gathered from people 20 years of age and older using standardised questionnaires, and ANOVA and multiple regression analysis were used for analysis. Environmental excitement, technical excitement, anxiety, social influence, social image, perceived benefits, performance expectancy, and conducive conditions are important factors taken into account. The results show that adoption intention is significantly shaped by social image, environmental concern, and performance expectations. Age and income, two demographic factors, did not, however, significantly alter perception. Policymakers and manufacturers can use the study’s practical lessons to create strategies that raise awareness, improve infrastructure, and match marketing to changing customer demands. India can become a leader in green mobility and hasten the adoption of electric vehicles with calculated efforts.